Evolution and Determinants of Health-Related Quality-of-Life in Kidney Transplant Patients Over the First 3 Years After Transplantation. Issue 3 (March 2016) - Villeneuve, Claire; Laroche, Marie-Laure; Essig, Marie; Merville, Pierre; Kamar, Nassim; Coubret, Anne; Lacroix, Isabelle; Bouchet, Stéphane; Fruit, Dorothée; Marquet, Pierre; Rousseau, Annick
Abstract : Background: Health-related quality of life (HRQOL) usually improved after kidney transplantation; however, a non-negligible number of patients did not benefit from transplantation in HRQOL. The aims of this cohort study were to describe the evolution of HRQOL in kidney transplant recipients to search for subgroups with distinct time profiles and to investigate these determinants. Methods: Three hundred thirty-seven adult patients were followed up from 1 to 36 months after kidney transplantation. Each patient completed repeated HRQOL assessments (median, 5; range, 2-9). K-means for longitudinal data was used to identify homogeneous clusters of HRQOL time profiles obtained for the mental and physical composite scores (MCS and PCS) and for the 8 dimensions of the short-form 36 scale. Covariates associated with these clusters were investigated using random forest analysis. Magnitude and shape of the HRQOL variations over time were investigated using linear regression mixed models. Results: Two longitudinal clusters were identified for the time profiles of PCS and MCS. Patients classified in the higher cluster (ie, 60% of the population) exhibited a steady-state HRQOL, similar on average to the general population, whereas in the lower cluster, PCS and MCS scores were significantly lower than in the general population. Muscular weakness in the first year after transplantation explained 19% of the interpatient variability of PCS 3 months after transplantation, whereas associated with anxiety, it explained 24% of interpatient MCS variability. Conclusions: This work suggests to promote (i) physical rehabilitation programs after transplantation to curb the muscular loss and (ii) systematic attention to the patient's anxiety. Abstract : Health-related Quality of Life (HRQOL) can be assessed by the mental composite score and the physical composite score, which improves for most patients after transplant. This prospective study shows that anxiety and muscle weakness are modifiable factors contributing to low HRQOL. Supplemental digital content is available in the text.